The Relationship Between Measures of Preservice Principal Practice and Future Principal Job Performance. (March 2022) - Doss, Christopher; Zaber, Melanie A.; Master, Benjamin K.; Gates, Susan M.; Hamilton, Laura S.
Principals are the second-largest school-based contributor to student achievement. Interventions focused early in the "pipeline" for identifying and developing effective principals might be a promising strategy for promoting principal effectiveness, yet no prior research has examined measures of principal performance during preservice preparation. We analyze 31 measures of principal practices developed by New Leaders and integrate into their year-long, preservice Aspiring Principals program. We link these measures to administrative data in nine districts to understand how they predict student and principal outcomes after candidate placement. We find associations with gains in student achievement on standardized tests, gains in student attendance, and higher rates of principal retention. We compare our results with studies of measures from licensure exams and evaluation systems.